2011
DOI: 10.1016/j.arcmed.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Candidate Gene Polymorphisms and Obesity in a Young Mexican-American Population from South Texas

Abstract: Background and Aims Obesity is increasingly a health problem and a risk factor for diabetes in young Mexican-American populations. Genetic association studies in older, mostly non-Hispanic populations have reported that polymorphisms in the candidate genes HSD11B1, CRP, ADIPOQ, PPARG, ANKK1, ABCC8 and SERPINF1 are associated with obesity or diabetes. We analyzed the polymorphisms rs846910, rs1205, rs1501299, rs1801282, rs1800497, rs757110 and rs1136287in these candidate genes, for association with obesity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 67 publications
1
29
0
6
Order By: Relevance
“…Although data from adults do not confirm direct effect of HSD11B1 polymorphisms on body mass, an association with obesity and its measures (BMI, WC, waist-to-hip ratio) was reported in Spanish, American and Chinese children [20,21,23]. Results with regard to insulin and its action are contradictory in Spanish and Mexican-American youth [20,22]. This latter cohort also revealed a relationship between HSD11B1 polymorphism and circulating triglycerides [22].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although data from adults do not confirm direct effect of HSD11B1 polymorphisms on body mass, an association with obesity and its measures (BMI, WC, waist-to-hip ratio) was reported in Spanish, American and Chinese children [20,21,23]. Results with regard to insulin and its action are contradictory in Spanish and Mexican-American youth [20,22]. This latter cohort also revealed a relationship between HSD11B1 polymorphism and circulating triglycerides [22].…”
Section: Discussionmentioning
confidence: 75%
“…In a small American study an association between an adenine insertion in HSD11B1 gene intron 3 (ins4436A, rs45487298) and increased BMI, waist-to-hip ratio and insulin resistance indices in children was found [21]. More recent analysis in young Mexican-Americans confirmed that rs846910 was associated with Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) and circulating triglycerides but not with obesity [22]. Finally, a Chinese study linked several HSD11B1 variants with childhood obesity and its cardiometabolic complications -hypertension, hypercholestarolaemia, and hyperglycaemia [23].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A Proteína C Reativa (PCR) é um marcador inflamatório importante e os níveis circulantes desta proteína podem ter um valor prognóstico na identificação de indivíduos com maior risco de desenvolver obesidade, diabetes mellitus tipo 2 e resistência à insulina, sendo que o gene da Proteína C Reativa (CRP) está associado com glicose em jejum alterada e resistência à insulina (DURAN-GONZALEZ et al, 2011 …”
Section: Introductionunclassified
“…58 In the Netherlands, the A1 allele frequency was 18.3% in obese children 59 and in NorthAmerican studies with obese children, it ranged from 17.0% 60 to 38.5%. 61 In a Brazilian study with obese and normal weight (controls) children, the A1 allele frequencies were 34.5% and 23.0%, respectively, and a statistically significant association between the A1 allele and obesity was verified.…”
Section: Drd2 Taqia Polymorphismmentioning
confidence: 99%